Preoperative fasting protects against renal ischemia-reperfusion injury in aged and overweight mice (2014)
Ischemia-reperfusion injury (IRI) is inevitable during kidney transplantation leading to oxidative stress and inflammation. We previously reported that preoperative fasting in young-lean male mice protects against IRI. Since patients are generally of older age with morbidities possibly leading to a different response to fasting, we investigated the effects of preoperative fasting on renal IRI in aged-overweight male and female mice. Male and female F1-FVB/C57BL6-hybrid mice, average age 73 weeks weighing 47.2 grams, were randomized to preoperative ad libitum feeding or 3 days fasting, followed by renal IRI. Body weight, kidney function and survival of the animals were monitored until day 28 postoperatively. Kidney histopathology was scored for all animals and gene expression profiles after fasting were analyzed in kidneys of young and aged male mice. Preoperative fasting significantly improved survival after renal IRI in both sexes compared with normal fed mice. Fasted groups had a better kidney function shown by lower serum urea levels after renal IRI. Histopathology showed less acute tubular necrosis and more regeneration in kidneys from fasted mice. A mRNA analysis indicated the involvement of metabolic processes including fatty acid oxidation and retinol metabolism, and the NRF2-mediated stress response. Similar to young-lean, healthy male mice, preoperative fasting protects against renal IRI in aged-overweight mice of both genders. These findings suggest a general protective response of fasting against renal IRI regardless of age, gender, body weight and genetic background. Therefore, fasting could be a non-invasive intervention inducing increased oxidative stress resistance in older and overweight patients as well. © 2014 Jongbloed et al.